Perencanaan Jalur Ganda (Double Track) Jalan Rel Ruas Semarang – Gubug - Christianto P. Adi; Erha Intan Sukmajati; Siti Hardiyati; Sri Prabandiyani Retno Wardani (Jurnal Karya Teknik Sipil, 2013)
Based on National Railways Master Plan (RIPNAS) of Directorate General of Railways Ministry of Transportation (2011), in 2030, number of railway pessangers in Java increased in the amount of 858.5 million people / year and freight in Java amounted to 534 million tons / year. Therefore, the government planed to develop the railway network in Java with Double Track program or multiple pathways in order to achieve optimal service, the development of a single track to double track between Semarang Tawang Station in Semarang until Gubug station in Grobogan were included. From the design performed, the double track alignment will be placed on the right side of the existed alignment in direction from Semarang to Gubug where there are more open land availability, with the new lines elevation as high as the existed lines elevation. Railway constructed in accordance with the first class  railway classification with R54 rails type, double elastic’s fastening system using Pandrol e-clip type with rubber pad, PT.WIKA Beton prestressed concrete sleppers N-67 type , upper ballast thickness of 30 cm and 15 cm thick sub ballast. Double track railway’s subgrade situated more on the fill positions between 30 cm to 165 cm height using retaining wall reinforcement. Side channel surface drainage with a rectangular cross section from reinforced concrete.